The Role of Society Toward Concervation - Mumpuni, Kistantia Elok; Susilo, Herawati; Rohman, Fatchur (Universitas Sebelas Maret, 2015)
Local potential is one of the useful thing of biological resources. The use of biological resources was done to fulfill the needs of human life. The necessities of life is going increase that causes exploitation of biological resources continue to be made in larger numbers. Therefore, conservation efforts must begin immediately. This study aimed to determine human role in conservation efforts. Descriptive exploratory study method was used to know the role of communities around Mountains of Muria in conservation efforts. This study discussed the potency and conservation of parijoto. Some conservation efforts was carried out to protect parijoto in the area of Mountains of Muria they are cultivation of local crops either independently or with the help of the government, the use of local wisdom, the establishment of forest and conservation communities which be founded by the Foundation of Sunan Muria, and the news media roles. The results showed a wide range of local community participation, private organizations, and governments in conservation efforts parijoto. It was an effort to save the preservation one of biological resources in Indonesia especially in area of Muria Mountain. Results were directing human relate conserve biological resources.Keywords: concervation, biological resources, role of society